Penggunaan Analisis Bibliometrik Untuk Mengidentifikasi Terobosan Penelitian Kaizen Tahun 2019-2024 Menggunakan Aplikasi Vosviewer - Gunawan, Ahmad; Sucipto, Imam (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study uses bibliometric analysis with the VOSViewer application to identify breakthroughs in Kaizen research in the period 2019 to 2024, a philosophy of continuous improvement that is the focus of research in various fields such as manufacturing, management, and engineering. Through searching, collecting, and evaluating Kaizen-related scientific publications, this study produced a scientific network map to visualize the relationship between articles and research contributions. Article data was obtained from the Google Schooler database using the Publish or Perish reference manager application. This search resulted in 200 articles that were considered relevant. These results show that the number of publications related to this topic from 2019 to 2024 is fairly large, with an average number of publications of 111.69. Then it is known that the highest number of publications is in 2020 with a total of 49 articles, while the lowest is in 2023 with 31 articles. Analysis of co-occurrence of keywords using VOSViewer resulted in 78 words/terms grouped into 8 clusters. The study results indicate that the author recommends include additional keywords in future research to enhance the accuracy and comprehensiveness of the findings. This review might serve as a starting point for further study on related materials.